Systematic review of reviews of symptoms and signs of COVID-19 in children and adolescents. Issue 8 (17th December 2020) - Viner, Russell M; Ward, Joseph Lloyd; Hudson, Lee D; Ashe, Melissa; Patel, Sanjay Valabh; Hargreaves, Dougal; Whittaker, Elizabeth
Abstract : Objective: To undertake a systematic review of reviews of the prevalence of symptoms and signs of COVID-19 in those aged under 20 years. Design: Narrative systematic review of reviews. PubMed, medRxiv, Europe PMC and COVID-19 Living Evidence Database were searched on 9 October 2020. Setting: All settings, including hospitalised and community settings. Patients: Children and young people (CYP) under age 20 years with laboratory-proven COVID-19. Study review, data extraction and quality: Potentially eligible articles were reviewed on title and abstract by one reviewer. Quality was assessed using the modified AMSTARS criteria and data were extracted from included studies by two reviewers. Main outcome measures: Prevalence of symptoms and signs of COVID-19. Results: 1325 studies were identified and 18 reviews were included. Eight were high quality, 7 medium and 3 low quality. All reviews were dominated by studies of hospitalised children. The proportion of asymptomatic CYP ranged from 14.6% to 42%. Fever and cough were the the most common symptoms; proportions with fever ranged from 46% to 64.2% and with cough from 32% to 55.9%. All other symptoms or signs including rhinorrhoea, sore throat, headache, fatigue/myalgia and gastrointestinal symptoms including diarrhoea and vomiting were infrequent, occurring in less than 10%–20%. Conclusions: Fever and cough are the most common symptoms in CYP with COVID-19, with other symptoms infrequent. Further research on symptoms in community samples are needed to inform pragmatic identification and testing programmes for CYP.